(untitled) (Proceedings of the International Conference on Future of Women, 2019)
This paper attempts to examine personal consciousness among policy actors towards Gender Responsive Budgeting (GRB) initiative in connection with gender equality in Malaysia. The paper concerns in assessing on personal consciousness as a part of challenges to implement GRB in the Ministry of Women, Family and Community Development (MWFCD) and Ministry of Finance (MOF). Available western studies have shown that GRB or gender budget processes still encounter various issues such as lack of concept understanding itself and support from the organisational top management. Malaysia’s GRB initiative was introduced in the mid-2003. Nevertheless, even after 12 years since successful of Manual on Gender Budgeting publication, a very low personal consciousness on gender related matters contribute to the least number of GRB and gender-related awareness programmes organised for policy actors. The low personal gender consciousness among policy actors was identified as an ultimate challenge in implementing GRB in Malaysia. In collecting data, this study has carried out a series of face-to-face interviews with eight top policy actors; and a desk review of various documents related to gender awareness and budgeting works. The data was analysed on personal consciousness which is the first quadrant of Individual and Organisational Change Matrix introduced by Rao and Kelleher (2002). The paper concludes that GRB initiative needs support and cooperation from various stakeholders to develop personal consciousness on gender among policy actors and enable them to have deep understanding on GRB processes. So, this paper recommends that the MWFCD and MOF need to enhance women participation in budgetary debates and decision making processes. Additionally, the top management of the ministries has to support the initiative through GRB’s advocacy, effective policy cascading as well as lobbying programmes related to gender understanding.